FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEGAWAI UNTUK MELAKUKAN WHISTLEBLOWING (STUDI PADA PEGAWAI BANK INDONESIA) - Hidayat, Gusti Wahyu; Hayat, Atma; Nor, Wahyudin (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2021)
The whistleblowing system is designed by an organization to report fraud. No matter how well the system is designed, if no one uses it to report fraud, the purpose of the system will not be achieved. This study aims to examine and analyze the effect of whistleblowing knowledge, perceptions of organizational protection to whistleblowers, perceptions of organizational support, the level of seriousness of fraud, and personal costs on employees' interest in whistleblowing on employees of Bank Indonesia. The data used are primary data collected using a questionnaire survey with google form and samples are determined using an accidental sampling technique.Â Data were analyzed using multiple linear regression techniques, processed using SPSS software. The results showed that whistleblowing knowledge, perceptions of organizational protection to whistleblowers, and the level of seriousness of fraud significantly affect employee interest in whistleblowing. In contrast, perceptions of organizational support and personal costs do not considerably affect employee interest in whistleblowing.